Mechanics and Pattern Transfer of Imprinted NiAl Amorphous Films Investigated Using Atomistic Simulation - Wu, Cheng-Da; Fang, Te-Hua; Ming-Hong-Lin; Su, Jih-Kai (Current Nanoscience, 2017)
Background: Amorphous NiAl alloys, whose atomic arrangement is disordered, have attracted a lot of attention due to their unique physical properties, such as high mechanical strength and hardness, high toughness, low friction, good corrosion resistance, and minimal shrinkage. The alloys have excellent corrosion resistance at high temperature and thus are often used in blade coatings. Nanoimprinting lithography (NIL) is an accessible and low-cost technique for fabricating various components on micro- and nanometer scales. Methods: The purpose of this work is to quantitatively study the forming and mechanics properties of the amorphous NiAl films during the NIL process utilizing the molecular dynamics (MD) simulations. The effects of taper angle of mold cavities, interval between mold cavities, and annealing temperature on amorphous NiAl films are studied. Results: The results are discussed in terms of atomic trajectories, shear strain, imprinting force, and elastic recovery of imprinted films. The study contributes to a better understanding of the amorphous material forming mechanisms and mechanics at the nanoscale. MD simulations were used to investigate the effect of taper angle of mold cavities, mold cavity interval, and annealing temperature on amorphous NiAl films. The required imprinting force and adhesion force between the mold and imprinted films increase with decreasing mold cavity interval. Conclusion: Undesired elastic recovery of patterns can be reduced by using molds with smaller taper angles and cavity intervals. During imprinting, film atoms with high shear strain values are mainly distributed in areas with a geometric discontinuity of mold, forming significant defects. Thermal annealing effectively decreases the shear strain of imprinted films; however, it increases the elastic recovery of patterns, especially in the area at the top of a pattern.
Keywords: NiAl